RESPON MASYARAKAT TERHADAP PASAR SENI DI KABUPATEN SIAK - Ice Muliana "; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at Kampung Dalam village. The purpose of this research is the background Kabuapaten in Siak art market and to know the public response to the change of traditional market into the art market Kampung Dalam village in Siak District Siak Regency. The focus topic of this research is the public response to the traditional market change into the art market in Siak Regency. The samples in this study amounted to 50 people. The authors use quantitative methods and use simple random sampling techniques. Data instruments are observations, polls and documentation. The research on public response to the art market in Siak Regency can be concluded that: The location of the art market, the research conducted found that 68.0% of respondents say locations of the art market are less strategic. Due to the less strategic location of the art market it has only 40% of merchants selling every day. 60% of merchants rarely open the Kiosk. The kiosk was managed, research found that 68.0% of respondents said the art market of Siak County did not develop, therefore 52% revealed that the art market became deserted visitors. Type of trade, researchers found that the most traded types of trades are handicrafts with a percentage of 80%, 12% are art tools, and 8% are a type of traditional art trading. The study also found public response to Siak County Art market as follows: positive response, 92.0% of respondents said the products sold in the art market in Siak District can introduce local cultures to the outside community. Negative response, 8% of respondents said the art market of Siak Regency was unable to provide the visitors with the needs well because the number of stalls active only slightly. Keywords: Community Response, Art Market